"Corps" leadership: a cadet perspective on shared leadership. Issue 3 (14th August 2017) - Martin, Ira H.; Prophet, Trevor; Owens, Christopher; Martin, JennyMae; Plummer, Gabe
Abstract : Purpose: The purpose of this paper is to enhance understanding of shared leadership in a military academy setting. Design/methodology/approach: A qualitative methodology was selected to ask senior cadets about a shared leadership concept at the United States Coast Guard Academy, known as the "corps leading the corps." Cadets responded to, "what does the corps leading the corps mean to you?" via a paper and pencil survey. Cadet responses were coded using content analysis. Findings: Three higher-order dimensions emerged from the data: autonomy and empowerment, developing self and others, and role modeling. Originality/value: The paper provides emerging leaders' commentary to incorporating a shared leadership concept within an educational environment.